Making Changes in the Course of a European Project and Infringements of Community Law - Szmyt, Władysław (University of Wroclaw. Faculty of Law, Administration & Economics, 2014)
This paper analyses issues concerning the utilization of European structural funds in Poland, where numerous dilemmas appear with in practice with procedures and details in the documentation of projects. One of these problems is that of the consequences of using components in the project which may be treated as counterparts or substitutes of the components specified in tender documentation. The beneficiaries of the project may believe that departure from the assumptions specified in the documentation may result in negative financial consequences imposed by the authorities responsible for management procedures of EU structural funds in Poland. The main question arises of which types of incident are treated as irregularities or infringements of Community law and EU budget regulations. Reviewing cases and rules of Community law shows that there is no cause to initiate legal proceedings in order to establish the presence of irregularities, and that the parties to project agreements tend to find compromise solutions but do not breach the general provisions of Community law.
Keywords: Polska; europejskie fundusze strukturalne; prawo wspólnotowe